Financialization in commodity markets - Varadarajan V. Chari; Lawrence J. Christiano (Federal Reserve Bank of Chicago, 2017)
The financialization view is that increased trading in commodity futures markets is associated with increases in the growth rate and volatility of commodity spot prices. This view gained credence because in the 2000s trading volume increased sharply and many commodity prices rose and became more volatile. Using a large panel dataset we constructed, which includes commodities with and without futures markets, we find no empirical link between increased futures market trading and changes in price behavior. Our data sheds light on the economic role of futures markets. The conventional view is that futures markets provide one-way insurance by allowing outsiders, traders with no direct interest in a commodity, to insure insiders, traders with a direct interest. The data are not consistent with the conventional view and we argue that they point to an alternative mutual insurance view, in which all participants insure each other. We formalize this view in a model and show that it is consistent with key features of the data.
Keywords: E02; G12; G23; 330; Spot Price Volatility; Futures Market Returns; Open interest; Net Financial Flows; Rohstoffderivat; Terminmarkt; Volatilität; Spotmarkt; Handelsvolumen der Börse; Schätzung; USA